An integrated green management model to improve environmental performance of textile industry towards sustainability. (20th October 2020) - Roy, Mousumi; Sen, Parag; Pal, Parimal
Abstract: As manufacturing of textile causes serious environmental damage in different ways, identification of the critical environmentally conscious manufacturing indicators (CECMI) is essential to formulate environmental strategies. However, lack of proper models to identify the CECMIs for the textile industries make this research area to explore further. A novel integrated model combining environmental process mapping (EPM), decision-making trail and evaluation laboratory (DEMATEL) and analytic network process (ANP) has been developed in this work and examined in the context of an Indian textile industry. While DEMATEL explains the cause and effect relationship, ANP calculates the weights of the indicators. Indicators such as waste generation, volatile organic compound (VOC) emission and energy consumption are found to be critical for the textile industry. Technical solutions are proposed here to solve the environmental problems related to the CECMIs. Implementation of the technical solutions results in reduction of 12% wastes, 10–11% carbon dioxide emission, 9–10% nitrogen oxide and 5% energy consumption while ensuring better occupational health (annual decrease of respiratory and allergic problems by 8% and 3% respectively). The work is thus expected to help develop sustainable environmental policy for the textile industries. Highlights: DEMATEL and ANP integrated to develop a new management model. Combined model succeeds in identifying the critical environmental performance indicators. The model shows a new approach in formulation of environmental policy.